Activity Report: Extreme weather events (drought) and its impact on assets, livelihoods and gender roles Case study of small-scale livestock herders in Cauca, Colombia - Arora, Diksha (2019)
Research suggests that extreme weather events have a negative impact on agricultural income and wellbeing of smallholder households. Climate change induced shocks can also a ect people's ability to work, thereby, in uence their decisions on labor or time allocation. Very few studies have considered this impact, mainly at the economy-wide level. There is a huge gap in the evidence of micro level impact of climate change on time-use among agricultural households. In this paper, I analyze the impact of a prolonged weather shock [drought] on labor allocation, primarily time-use of small- scale livestock herders. Adopting a gender lens to the analysis, the paper examines gender di erences in the e ects of the climate shock. The ndings suggest that although both men and women became time poorer as a result of coping with the e ects of the drought, women who already managed the double burden of productive and reproductive activities became worse o .